Multigenic truncation of the semaphorin–plexin pathway by a germline chromothriptic rearrangement associated with Moebius syndrome. Issue 8 (14th May 2019) - Nazaryan‐Petersen, Lusine; Oliveira, Inês R.; Mehrjouy, Mana M.; Mendez, Juan M. M.; Bak, Mads; Bugge, Merete; Kalscheuer, Vera M.; Bache, Iben; Hancks, Dustin C.; Tommerup, Niels
Abstract: Moebius syndrome (MBS) is a congenital disorder caused by paralysis of the facial and abducens nerves. Although a number of candidate genes have been suspected, so far only mutations in PLXND1 and REV3L are confirmed to cause MBS. Here, we fine mapped the breakpoints of a complex chromosomal rearrangement (CCR) 46, XY, t(7;8;11;13) in a patient with MBS, which revealed 41 clustered breakpoints with typical hallmarks of chromothripsis. Among 12 truncated protein‐coding genes, SEMA3A is known to bind to the MBS‐associated PLXND1. Intriguingly, the CCR also truncated PIK3CG, which in silico interacts with REVL3 encoded by the other known MBS‐gene REV3L, and with the SEMA3A/PLXND1 complex via FLT1. Additional studies of other complex rearrangements may reveal whether the multiple breakpoints in germline chromothripsis may predispose to complex multigenic disorders. Abstract : Moebius syndrome (MBS) is a congenital disorder caused by paralysis of the facial and abducens nerves. Although a number of candidate genes have been suspected, so far only mutations in PLXND1 and REV3L are confirmed to cause MBS. Here, we fine mapped the breakpoints of a complex chromosomal rearrangement (CCR) 46, XY, t(7;8;11;13) in a patient with MBS, which revealed 41 clustered breakpoints with typical hallmarks of chromothripsis. Among 12 truncated protein‐coding genes, SEMA3A is known to bind to the MBS‐associated PLXND1. Intriguingly, the CCR also truncated PIK3CG, which in silico interacts with REVL3 encoded by the other known MBS‐gene REV3L, and with the SEMA3A/PLXND1 complex via FLT1. Additional studies of other complex rearrangements may reveal whether the multiple breakpoints in germline chromothripsis may predispose to complex multigenic disorders.